Habituation Method In Developing The Religiosity Dimensions for Young Children - Issaura Dwi Selvi; Maragustam Siregar; Zulfadhly Mukhtar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
ABSTRACTThe challenge of developing religious values today is consistency and long-term memory. Because the development of religious values will be valid for the whole life of the child. This study aims to show habituation methods that can be used in developing dimensions of religiosity in the golden age. This research was conducted using qualitative research through a phenomenological approach. The respondents in this study were teachers and children in TK ABA Rewulu Kulon Yogyakarta. Techniques used for data collection with Focus Group Discussions, interviews and observations, while in analyzing data with data reduction, visualization, and data verification. The research obtained data that in carrying out the habituation method, it was carried out with several programs of habituation activities, namely dhuha prayers, almsgiving, memorization of prayers and hadith, studying and memorizing by applying the concept of Wafa Learning. The habituation method by applying several programs has been proven to build a dimension of religiosity for children faster, quality, fun and long-term. Application that is carried out consistently can build the dimendi of children's religiosity more optimally.Keyword: Early Childhood; Habituation Methods; Religiosity Dimension